2023
DOI: 10.2147/dmso.s420872
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Sensitivity to Thyroid Hormones and Metabolic Dysfunction-Associated Fatty Liver Disease in Euthyroid Subjects: A Cross-Sectional Study

Abstract: Thyroid hormones (THs) exert instrumental effects in regulating lipids metabolism. Whereas, research investigating the relationship between sensitivity indices to THs and metabolic dysfunction-associated fatty liver disease (MAFLD) have contradicted this. This study was designed to approach the correlation between sensitivity indices to THs and MAFLD in euthyroid subjects. Methods: An overall sample of 6356 euthyroid participants were enrolled in a Chinese hospital. Free triiodothyronine to free thyroxine rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 61 publications
(69 reference statements)
0
8
0
Order By: Relevance
“…Liu H, 2023 [111] Cross-Sectional Study 6356 euthyroid adults, 2191/6356 with MAFLD Elevated levels of FT3/FT4 and TFQIFT3 were significantly associated with the prevalence of MAFLD in euthyroid populations. The TyG index partially mediated the relationship between FT3/FT4, TFQIFT3, and MAFLD.…”
Section: Reference Study Type Population Main Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Liu H, 2023 [111] Cross-Sectional Study 6356 euthyroid adults, 2191/6356 with MAFLD Elevated levels of FT3/FT4 and TFQIFT3 were significantly associated with the prevalence of MAFLD in euthyroid populations. The TyG index partially mediated the relationship between FT3/FT4, TFQIFT3, and MAFLD.…”
Section: Reference Study Type Population Main Resultsmentioning
confidence: 99%
“…Even in an euthyroid population, Liu H. et al found that MAFLD prevalence was 34.47%. This research study showed that the MAFLD group was characterized by a higher total triiodothyronine resistance index (TT3RI), thyroid feedback quantile-based index (TFQI)FT3, and FT3/FT4 levels in comparison with the non-MAFLD group, where TT3RI stands for fT3/TSH; TFQIFT3 stands for the thyroid feedback quantile-based index (TFQI)] = fT3 − (1-TSH), underlining the bond between hypothyroidism and MAFLD [111].…”
Section: Clinical Evidencementioning
confidence: 97%
“…Recently, Liu et al published an original article titled “Association Between Sensitivity to Thyroid Hormones and Metabolic Dysfunction-Associated Fatty Liver Disease in Euthyroid Subjects: A Cross-Sectional Study” in Diabetes, Metabolic Syndrome and Obesity-Targets and Therapy. 1 Since we are undertaking a pertinent longitudinal cohort study, we are highly interested in this article. We appreciate the authors for their work and congratulate them on their successes.…”
Section: Dear Editormentioning
confidence: 99%
“…
in Diabetes, Metabolic Syndrome and Obesity-Targets and Therapy. 1 Since we are undertaking a pertinent longitudinal cohort study, we are highly interested in this article. We appreciate the authors for their work and congratulate them on their successes.This study focused primarily on the current hotspot of metabolic dysfunction-associated fatty liver disease (MAFLD) and explored the relationship between thyroid hormone and MAFLD.
…”
mentioning
confidence: 99%
“…Low free triiodothyronine (FT3) level was negatively associated with the severity of CAD in euthyroid individuals ( 9 ). The TyG index, as an effective indicator of metablic syndrome, has been proven to be related to THs and THs sensitivity ( 10 ). Previous studies also investigated the relationship between THs and TyG index in non-diabetic adults and showed TyG index was negatively associated with FT4 level, positively associated with TSH level ( 11 ).…”
Section: Introductionmentioning
confidence: 99%